Adopsi Pendekatan Pengembangan Pasar (Market Development) Pada Sub Sektor Kopi Arabika Dataran Tinggi Kabupaten Garut - Dani Hamdan (LPPM UNINUS, 2017)
Arabica coffee in Garut plateau is a smallholder plantation sub-sector that has market growth, but is less balanced with upstream growth. The approach for this sub-sector should be comprehensive covering upstream began with the superior coffee plantations to downstream in form of ready-to-eat coffee products for consumers, in order to increase added value for business actors along the coffee chain. The